Understanding the skin blackening phenomenon in Youzhou Dark goats based on the histological characteristics of melanocytes - Chen, Cancan; Li, Jie; Sun, Xiaoyan; Jiang, Jing; Lv, Shipeng; Liu, Liangjia; Wang, Gaofu; Ren, Hangxing (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The study was conducted to identify the molecular mechanism of the phenotype formation of Youzhou black sheep by histological cytology and transcriptomics. Materials and Methods: In this study, HE and IHC staining were used to explore the patterns and cytological differences in skin pigment deposition between Youzhou Dark goats and Banjiao goats. In addition, the DEGsrelated to the black skin phenotype were identified via transcriptomic analyses. Finally, the expression pattern of the agouti signal protein (ASIP) gene in the skin from individuals with different skin color phenotypes was verified by FISH. Results: The resultsshowed that compared with that on the skin surface of Banjiao goats, melanin deposition on the skin surface of Youzhou Dark goats was abnormally increased. The transcriptomic analyses showed that the expression of the ASIP genes decreased significantly in Youzhou Dark goats. FISH confirmed that the expression of the ASIP gene in Youzhou Dark goats was significantly lower than that in Banjiao goats. Conclusion: The present study showed that a decrease in ASIP gene expression and an increase in melanin production are important factors associated with skin pigmentation in Youzhou Dark goats. J. Adv. Vet. Anim. Res., 11(4): 1139–1148, December 2024 http://doi.org/10.5455/javar.2024.k865